Introduction to enzyme and coenzyme chemistry - Bugg, Tim. (Chichester, West Sussex : Wiley, 2012)
Looking at enzymes from an organic chemistry perspective, this updated reference includes information on recent advances in our understanding of enzyme action; topical examples to illustrate key points; two-color figures of the active sites of enzymes discussed in the text to illustrate the interplay between enzyme structure and function; and end-of-chapter problems to allow readers to check their understanding of the material. This concise but comprehensive guide is essential for undergraduate and postgraduate students of organic, bio-organic, and medicinal chemistry, chemical biology, bioche.
The Metallo-proteasesThe Aspartyl Proteases; CASE STUDY: HIV-1 protease; 5.3 Esterases and lipases; 5.4 Acyl transfer reactions in biosynthesis (coenzyme A); 5.5 Enzymatic phosphoryl transfer reactions; 5.6 Adenosine 5'-triphosphate (ATP); 5.7 Enzymatic glycosyl transfer reactions; 5.8 Methyl group transfer: use of S-adenosyl methionine and tetrahydrofolate coenzymes for one-carbon transfers; 6 Enzymatic Redox Chemistry; 6.1 Introduction; 6.2 Nicotinamide adenine dinucleotide-dependent dehydrogenases; 6.3 Flavin-dependent dehydrogenases and oxidases; 6.4 Flavin-dependent mono-oxygenases.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Enzymes; Coenzymes; MEDICAL -- Biochemistry; Coenzymes; Enzymes; Electronic books